Repulsive van der Waals forces enable Pickering emulsions with non-touching colloids. Issue 35 (13th July 2016) - Elbers, Nina A.; van der Hoeven, Jessi E. S.; de Winter, D. A. Matthijs; Schneijdenberg, Chris T. W. M.; van der Linden, Marjolein N.; Filion, Laura; van Blaaderen, Alfons
Abstract : Repulsive van der Waals forces can prevent interfacial colloids from being wetted by the aqueous phase, resulting in a 'non-touching' system. Abstract : Emulsions stabilized by solid particles, called Pickering emulsions, offer promising applications in drug delivery, cosmetics, food science and the manufacturing of porous materials. This potential stems from their high stability against coalescence and 'surfactant-free' nature. Generally, Pickering emulsions require that the solid particles are wetted by both phases and as a result, the adsorption free energy is often large with respect to the thermal energy ( k B T ). Here we provide the first experimental proof for an alternative scenario: non-touching (effectively non-wetting), charged, particles that are completely immersed in the oil phase through a balance of charge induced attractions and repulsions caused by van der Waals forces. These particles nonetheless stabilize the emulsion. The main advantage of this novel adsorption mechanism is that these particles can easily be detached from the interface simply by adding salt. This not only makes the finding fundamentally of interest, but also enables a triggered de-emulsification and particle recovery, which is useful in fields like enhanced oil recovery, heterogeneous catalysis, and emulsion polymerization.